Comparison of objective and subjective resistance training quantification - Brown, N.; Bubeck, D.; Alt, W. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Quantification of training intensity in resistance training is difficult, since there are no valid objective methods to monitor how hard a subject is working during a training session (McGuigan et al., 2004). Therefore various authors recommend the use of the RPEscale (Singh et al., 2007; McGuigan et al., 2004). Although recommended, it is unclear which objective biomechanic or physiologic parameters the RPE represents. Chen et al. (2002) compared RPE and different physiologic parameters. No significantly high correlations were found. The purpose of this study was to determine if RPE is related to objective mechanic parameters during training sessions and to analyse if a difference in RPE between two intensities can be found. Methods: The subjects (n=13, 69% male, age=24.69 years) had at least one year of strength training experience and were randomly assigned to two groups (g1: n=8, g2: n=5) providing a cross-over design for the different training protocols. Subjects performed 10 training sessions (5 hypertrophy 8-12RM (HYP), 5 strength 1-3RM protocol (MAX)) with 10 standard exercises. After each training session-RPE was measured 30 minutes after the end of the exercise. Training load, number of repetitions, contraction mode, RPE-AM (active muscle) and recovery times were protocolled for each set and exercise during the training session. Pearson correlation coefficients were calculated between RPE, objective protocolled training parameters and RPEAM. A Wilcoxon signed rank test was used to determine differences in RPE between the two training protocols. Results: No statistical significant correlations were found between RPE and the objective training parameters. Correlations between session RPE and RPE-AM were low (r=0.45+-0.39). A significant difference in session RPE between the two training protocols was found (HYP= 6.30+-1.74, MAX= 4.47+-2.17, p<0.01). Discussion: A correlation between an objective training parameter and subjective training quantification using RPE could not be found. Therefore a more complex interaction of objective training parameters is assumed. In agreement with the findings of Chen et al. (2002) the representational factor of the RPE remains unclear. In this study a difference between HYP and MAX-protocol was found to be consistent with the findings of Singh et al. (2007). However, in our study MAX produced lower RPE values than HYP, which is contrary to recent findings. Further research should focus on the development of a valid and reliable objective quantification method, since quantification of resistance exercise using subjective measurements is critical.